Peran penting keluarga dan petugas kesehatan terhadap keteraturan pengobatan tuberkulosis - Rustiasari, Dwi Nisa; Hikmawati, Isna; Handayani, Diyah Yulistika; Setiyabudi, Ragil (Holistik Jurnal Kesehatan, 2025)
Background: Tuberculosis cases are still high due to low treatment success rates. Data shows that the treatment success rate in Indonesia in 2022 was 86.5%, not reaching 90% of the national target. Non-compliance with treatment in pulmonary TB patients is influenced by several factors, namely contact with patients, treatment process, health services, and socio-cultural factors. Purpose: To determine the role of family and health workers in the regularity of tuberculosis treatment. Method: Quantitative research with a cross-sectional approach was conducted on tuberculosis patients in the working area of ​​the Purwokerto Selatan Health Center, Banyumas Regency, Central Java in July-August 2024. The sample in this study was calculated using the population proportion formula and 99 respondents were obtained with inclusion criteria being people who were undergoing tuberculosis treatment, had no history of comorbidities, and did not experience mental disorders. The data analysis used was univariate and bivariate Spearman Rank analysis. Results: Based on the age of respondents, they are dominated by adults (19-59) with regularity in taking medication as many as 56 respondents (76.7%). The majority are male with regularity in taking medication as many as 40 respondents (54.8%), knowledge of respondents in the good category 65 (89.1%) regularly take medication, but there are still 17 respondents (65.4%) with good knowledge but do not regularly take medication. Motivation is dominant in the good category with a total of 40 respondents (54%), good family support as many as 55 respondents (75.3%) have regularity in taking medication, and support from health workers in the good category as many as 67 respondents 91.7% regularly take medication. The p-value for the variables of knowledge, family support, and health worker support <α 0.05, while the variables of age, gender, and motivation obtained p-values> 0.05. Conclusion: The variables of knowledge, family support, and health workers show a significant relationship with regularity in taking medication (p-value <0.05). Meanwhile, the variables of age, gender, and motivation did not show a significant relationship with the regularity of tuberculosis patient treatment (>0.05).   Keywords: Family Role; Health Workers; Regularity of Treatment; Tuberculosis.   Pendahuluan: Kasus tuberkulosis masih tinggi karena tingkat keberhasilan pengobatan yang rendah. Data menunjukkan bahwa angka keberhasilan pengobatan di Indonesia pada tahun 2022 adalah 86.5%, belum mencapai 90% dari target nasional. Ketidakpatuhan berobat pada penderita TB paru dipengaruhi oleh beberapa faktor yaitu kontak dengan pasien, proses pengobatan, pelayanan kesehatan, dan faktor sosio-budaya. Tujuan: Untuk mengetahui peran keluarga dan petugas kesehatan terhadap keteraturan pengobatan tuberkulosis. Metode: Penelitian kuantitatif dengan pendekatan cross-sectional, dilakukan kepada pasien tuberkulosis di wilayah kerja Puskesmas Purwokerto Selatan, Kabupaten Banyumas, Jawa Tengah pada bulan Juli-Agustus 2024. Sampel pada penelitian ini dihitung menggunakan rumus the population proportion formula dan didapatkan sebanyak 99 responden dengan kriteria inklusi adalah orang yang sedang menjalani pengobatan tuberkulosis, tidak ada riwayat penyakit penyerta, dan tidak mengalami gangguan jiwa. Analisis data yang digunakan adalah univariat dan analisis bivariat Spearman Rank. Hasil: Berdasarkan usia responden didominasi oleh usia dewasa (19-59) dengan keteraturan minum obat sebanyak 56 responden (76.7%). Mayoritas adalah laki-laki dengan keteraturan minum obat sebanyak 40 responden (54.8%), pengetahuan responden dalam kategori baik 65 (89.1%) teratur minum obat, namun masih terdapat 17 responden (65.4%) dengan pengetahuan baik tidak teratur minum obat. Motivasi dominan pada kategori baik dengan jumlah 40 responden (54%), dukungan keluarga baik sebanyak 55 responden (75.3%) memiliki keteraturan dalam minum obat, dan dukungan petugas kesehatan berada pada kategori baik sebanyak 67 responden 91.7% teratur dalam minum obat. Nilai p pada variabel pengetahuan, dukungan keluarga, dan dukungan petugas kesehatan < α 0.05, sedangkan variabel umur, jenis kelamin, dan motivasi diperoleh nilai p >0.05. Simpulan: Variabel pengetahuan, dukungan keluarga, dan petugas kesehatan menunjukkan hubungan yang signifikan dengan keteraturan berobat (p-value <0.05). Sementara itu, usia, jenis kelamin, dan motivasi tidak menunjukkan hubungan yang signifikan dengan keteraturan berobat pasien tuberkulosis (>0.05).   Kata Kunci: Keteraturan Pengobatan; Peran Keluarga; Petugas Kesehatan; Tuberkulosis.